Kefahaman Terhadap al-Asma’ al-Husna dan Kaitannya Dengan Ciri al-Ikhlas Menurut al-Ghazali Dalam Kitab al-Maqsad al-Asna: Understanding al-Asma’ al-Husna and Its Relation with the Implementation of al-Ikhlas (Sincerity) according to al-Ghazali’s Thought in al-Maqsad al-Asna - Shuhari, Mohd Hasrul; Hamat, Mohd Fauzi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2017)
The understanding of al-Asma’ al-Husna is important in Islam, as clearly indicated in the hadith of the Prophet (P.B.U.H). Any direction and instruction from the Prophet (P.B.U.H) have its significant benefits and advantages to individuals, especially Muslims. Among these benefits is inculcating the characteristics of al-ikhlas (sincerity) in the mind of Muslims. Thus, this article aims at examining al-Ghazali’s explanation of the methods of understanding al-Asma’ al-Husna. The article also aims at clarifying the correlation between the understanding of al-Asma’ al-Husna and the characteristics of sincerity in Muslim individuals. The collected data is based on content analysis research on al-Maqsad al-Asna fi Sharh Asma’ Allah al-Husna. The article concludes that a true comprehension of al-Asma’ al-Husna, according to al-Ghazali’s thought in al-Maqsad al-Asna, is capable of developing Muslims’ ikhlas (sincerity) because of the correlation between the understanding of al-Asma’ al-Husna and al-ikhlas (sincerity).